(untitled) (Fourth World Journal, 2025)
Background: Assessment instruments used in human services settings are often normed for majority populations. The importance of increasing the evidence-based validity of assessment tools in unique populations is essential to providing relevant evaluation, successful treatment, and, ultimately, individual and societal wellness. The Global Appraisal of Individual Needs (GAIN) is a comprehensive biopsychosocial assessment used with both adolescents and adults being admitted to substance abuse treatment in outpatient, intensive outpatient, partial hospitalization, methadone, short-term residential, long-term residential, therapeutic community, and correctional program settings. The GAIN has been used by agencies and systems of care in communities ranging from large urban areas to moderate-sized and small urban communities, rural areas, and Indian reservations. Over the past 10 years, several culturally focused workgroups have convened and given separate presentations about their use of the GAIN and related GAIN findings for their culturally distinct groups. Recently, those groups came together collectively–for the first time–to discuss GAIN administration and interpretation with diverse populations. Methods: Using qualitative methods based in grounded theory, this study identified the commonalities, themes, processes, experiences, and perceptions represented by the multiple diverse workgroups sharing their “in the field” or “practice based” knowledge of the GAIN process from a cultural standpoint. Results: Findings suggest the importance of assessment flexibility, the use of storytelling to improve communication-style differences, the importance of diversity trainings and respectful community relationship-building to increase the acceptance, utilization, and validity of the GAIN among diverse population groups. Conclusions: The findings provide multi-cultural and culturally distinct settings with meaningful information that can be useful for using the GAIN in culturally sensitive landscapes.